(untitled) (Universal International Scientific Journal, 2026)
This article covers the theoretical foundations of innovative psychological approaches used to scientifically analyze psychological stresses and stress factors that arise in students’ academic activities in the context of globalization, and their impact on their mental health, as well as to form students’ stress tolerance and maintain and strengthen their mental health.